Improving quality of care for perinatal and newborn care at district and subdistrict hospitals in Haryana, India: Implementation research protocol. (29th August 2018) - Das, Manoja Kumar; Arora, Narendra Kumar; Dalpath, Suresh; Kumar, Saket; Qazi, Shamim A.; Bahl, Rajib
Abstract: Aim: This implementation research aims to improve quality of care for mothers and newborns in three districts of Haryana, India at different public health facilities. Background: The decline in key maternal and newborn health indicators in India is relatively slower than expected and missed the millennium development goals. The multifold rise in institutional delivery in last decade has limited impact on neonatal and maternal mortality. Despite investments in infrastructure, equipment, supplies, monitoring tools, and also manpower, suboptimal gains in indicators point towards potential challenge in quality of care. Design: This study adopts pre‐post, quasi‐experimental study design with repeated observations using mixed research methods to document the impact of the plan‐do‐study‐act implementation cycles. Methods: The quality improvement interventions shall be implemented at three district hospitals and six‐first referral unit hospitals in three districts of Haryana targeting the antenatal, delivery, newborn care services with nurses as the key partners. Formative research, situational analysis, and root‐cause analysis shall inform the contextualization, prioritization of interventions. Incremental plan‐do‐study‐act cycles over 15 months shall be implemented. The changes in adherence to protocols, appropriate documentation, reduction in delays, and client satisfaction shall be documented for 16 indicators across delivery, antenatal, and sick newborn care domains. Discussion: The successful implementation of the quality improvement processes has the potential of improving the pregnancy outcomes in terms of stillbirths, maternal, and newborn mortality and sick newborn outcomes. The feasibility and learning of coimplementation in the public health system shall inform integration into standards and scaling up.